A New Quasi Open Loop Synchronization Technique for Grid-Connected Applications - Chedjara Zakaria; Massoum Ahmed; Wira Patrice; Safa Ahmed; Gouichiche Abdelmadjid (Electrical, Control and Communication Engineering)
This paper presents an effective quasi open-loop (QOLS) synchronization technique for grid -connected power converters that is organized in two different blocks. The first block is a new flexible technique for extracting the positive and negative sequence voltage under unbalanced and distorted conditions. It is a decoupled double self-tuning filter (DD-STF) or multiple self-tuning filters (M-STF) according to the conditions. The main advantages of this technique are its simple structure and the fact of being able to work under highly distorted conditions. Each harmonic is separately treated and this allows for selective compensation in active filter applications. The second block is the frequency detector; we propose a neural approach based on an ADALINE for online adaptation of the cut-off frequency of the DD-STF and M-STF considering a possible variation in the main frequency. The main advantage of this method is its immunity to the voltage signal amplitude and phase. In order to improve the performance of the frequency estimation under distorted source voltage, a pre-filtering stage is introduced. Experimental tests validate the proposed method and illustrate all its interesting features. Results show high performance and robustness of the method under low voltage ride through.